Buckling of stainless steel spherical caps subjected to uniform external pressure. (3rd October 2018) - Zhang, Jian; Wang, Yueyang; Wang, Fang; Tang, Wenxian
ABSTRACT: This study focused on the buckling of stainless steel spherical caps under uniform external pressure. Caps with a circular arc meridian have a nominal base diameter of 146 mm, nominal uniform wall thickness of 1 mm and nominal height of 37 mm. Six nominally identical laboratory-scale caps were fabricated, measured precisely and tested slowly. The buckling performances of such caps were studied experimentally and numerically, and the results show good agreement with each other. Furthermore, the buckling of 13 mass-equivalent caps of various heights were numerically analysed to identify the cap with the best load-carrying capacity. The results suggest that a spherical cap with height-to-base diameter ratio of 0.274 supports the highest buckling load. Such a cap can be applied as an end-closure for cylindrical pressure hulls or as a manhole cover for manned cabins in deep-sea vehicles.